Hydrophilic regulated photocatalytic converting phenol selectively over S-scheme CuWO4/TiO2. (1st October 2022) - Bai, Xue; Fu, Zhongyuan; Ma, Xinyi; Zhang, Zhe; Fan, Jun; Liu, Enzhou; Li, Jianli
Abstract: Heterojunction construction is regarded to be among the most promising pathways for photocatalytic H2 evolution and organic conversion. Herein, precursor of CuWO4 (P-CWO) and CuWO4 (CWO) were fabricated via low temperature hydrothermal as well as high temperature calcination method, respectively. P–CuWO4 /TiO2 (P-CWO/T) and CuWO4 /TiO2 (CWO/T) heterojunctions were consequently obtained through simple mechanical mixing with TiO2 . In light the S-scheme electron-hole separation and superior photocatalytic redox ability, the H2 evolution rate was found to increase to 6169.25 and 6026.8 μmol g −1 ·h −1, which was over 26 times higher than that of pure TiO2 under a 300 W Xe lamp in the range of 350–780 nm. P-CWO/T tend to produce more ·OH due to the surface bound H2 O and hydroxyl ligand. Particularly, closely related to the proportion of ·OH and ·CH3 active radicals, selective conversion of phenol can be controlled to 4-hydroxy-3-methylbenzoic acid and 2-methylbenzene-1, 4-diol respectively. This work not only presents unique S-scheme heterojunction in improving photocatalytic efficiency but also offers a selective route for the conversion of phenol in the perspective of active free radicals. Graphical abstract: Photogenic radical pathway of P-CWO/T and CWO/T S-scheme heterojunction and the mechanism for photocatalytic H2 evolution and selective organic conversion. Image 1 Highlights: Hydrophilic regulated S-scheme CuWO4 /TiO2 nanocomposites construction. Exploring the relationship between ·OH producing and surface bound H2 O was first reported. CuWO4 /TiO2 photocatalytic converting phenol selectively in the perspective of active free radicals.